Major Volatile Chemical Compounds of Agarwood Oils From Malaysia Based On Z-Score Technique - Nurlaila, Ismail; Nor Azah, Mohd Ali; Mailina, Jamil; Mohd Hezri Fazalul, Rahiman; Mohd Nasir, Taib; Saiful Nizam, Tajuddin (Springer Science, 2015)
Agarwood oil has been widely used in a number of different applications, including its use as a perfumery ingredient in incense products and a therapeutic agent in traditional medicines [1–8]. The oil itself can be obtained from the scented wood of plants belonging to the Aquilaria species (Thymelaeaceae) [1]. Agarwood oil consists of a complex mixture of chemicals, including sesquiterpenes, oxygenated sesquiterpenes, and chromone derivatives 7–9. These compounds can be used to differentiate agarwood oil into different grades and therefore have a significant impact on its quality and commercial value [8]. Many factors can influence the quality of agarwood oil, but the two most important are the chemical composition of the oil and the temperature used during the extraction of the oil from plant material [8, 10].